Alkali extraction of rice residue protein isolates: Effects of alkali treatment conditions on lysinoalanine formation and structural characterization of lysinoalanine-containing protein. (30th September 2018) - Zhang, Zhaoli; Wang, Yang; Dai, Chunhua; He, Ronghai; Ma, Haile
Highlights: Maximum amount of lysinoalanine was generated in 0.09 M NaOH at 75 °C for 120 min. Lysinoalanine formation was related to a decrease in cystine, lysine and threonine. The increase in alkali concentration leads to a decrease in α-helix and β-turn. Alkali concentration, temperature and time affect surface roughness of the protein. Abstract: The influence of alkali extraction conditions on the formation of lysinoalanine (LAL) and the structural characterization of lysinoalanine-containing protein in rice residue protein isolates (RRPI) were explored in this study. It was found that LAL content increased from 0.256 to 13.079 g/kg as NaOH concentration increased from 0.03 to 0.09 M and then decreased to 1.541 g/kg at 0.13 M NaOH. The extraction temperature and time were found to have a positive correlation with LAL content. The highest LAL content (25.679 g/kg) was observed with alkali extraction using 0.09 M NaOH at 75 °C for 120 min. The comparative structural analysis results showed that alkali treatment could degrade cystine, lysine, threonine and arginine to generate LAL; increasing alkali content would cause variations in secondary structure and micropore appearance on the surface of lysinoalanine-containing protein, whereas increasing alkali treatment temperature and time could enlarge the surface particle size of the protein.